IFRS adoption in developing countries: the case of Romania - Mihaela Ionascu; Ion Ionascu; Marian Sacarin; Mihaela Minu (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The purpose of the paper is to discuss the introduction of IFRSs within the social history of the modernization of Romanian economy and society, and to investigate the extent to which the potential benefits expected from their adoption are starting materialize. Based on an extensive literature review, we find that, at this stage, the stream of research investigating the impact of IFRS adoption in Romania is in its incipient stage, mainly consisting of studies of perception (of preparers, regulators, auditors and users), rather than studies focusing on providing empirical evidence on the actual consequences of IFRS implementation. However, results obtained so far show that the Romanian economic environment is to a certain degree open to IFRS and optimistic about their potential, although there are compliance issues and institutional factors that can diminish their benefits. There are also preliminary empirical results documenting an increase in transparency and in value relevance of financial information and a decrease in the cost of capital.
Keywords: M41; 650; IFRS; Romania; developing countries; cost and benefits; level of compliance